THE EFFECTIVENESS OF LEARNING MANAGEMENT IN MIN 6 TAPANULI TENGAH - Nurfauziah, Nurfauziah (Faculty of Tarbiyah nad Teacher Training, 2023)
This study aims to describe the level of effectiveness of public relations management implemented at MIN 6 Tapanuli Tengah, as well as to analyze the process of implementing community relations management can be achieved. The data collection technique used the interview method. This study uses a qualitative approach with a descriptive study method. The research data were obtained from observation guide sheets, interview guidelines, documentation. The results obtained from this research are first, there is good cooperation from all educators and teaching staff as well as management, especially public relations so that there is good communication to parents and the community; and second, there are tangible results when public relations is carried out properly in accordance with what has been programmed, it will get support from the head of the madrasa.